Affect of abjection in T. S. Eliot’s the waste land - Sharma, Madhukar (Journal of Tikapur Multiple Campus, 2017)
This paper deals with affect of abjection pervasive in modern people enunciated in T.S. Eliot's magnum opus The Waste Land (1922). This poem primarily enacts the poet's disgust with growing modernity of his time particularly relating to the declining of religion and the rise of sexual immorality. This research paper argues that this unhappiness swells in the force of disgust on the part of the poet at the immoral, unfulfilling sexual indulgence appearing repetitively in the text. It tries to unfold this disgust in terms of what Julia Kristeva calls the power (affect) of abjection. The assumption is that Eliot communicates his abjection through the tool of irony, which makes the readers be intensely aware of disgust at the soulless, mechanical sexual acts.